All-Dielectric Nanoresonators for χ(2) Nonlinear Optics - Gigli, Carlo; Marino, Giuseppe; Borne, Adrien; Lalanne, Philippe; Leo, Giuseppe (Frontiers in Physics, 2019)
Metal-less nanophotonics offers new opportunities for nonlinear optics with respect to waveguides, and advancements in nanofabrication enabled the development of dielectric subwavelength Mie-type structures. Here we review recent results on second harmonic generation with semiconductor nanoresonators, focusing on their Mie-scattering features in terms of efficiency and control over radiation pattern. Firstly, two theoretical models are comparatively discussed, with a view to possible improvements in analysis and design. Then some relevant experiments are reported, and the origin of χ(2) generation is discussed, outlining the main open topics to investigate in the next future and the advantages offered by these nanostructures to develop novel photonic devices.